ISTSat‐1, a space‐based Automatic Dependent Surveillance‐Broadcast demonstration CubeSat mission. (22nd January 2022) - Monteiro, João P.; Cunha, Alberto; Silva, Alexandre; Fernandes, Carlos; Neves, Diogo; Naf, Fabian; Tavares, Gonçalo; Freitas, José; Pinto, João; Piedade, Moisés; Ramos, Nuno; Gil, Paulo J. S.; et al.
Summary: The use of space‐based Automatic Dependent Surveillance‐Broadcast (ADS‐B) receivers to extend aircraft surveillance beyond line‐of‐sight communication has been discussed since the late 2000s and has been demonstrated in various missions. Although recent demonstrations have relied on small CubeSat platforms, the use of the smallest possible form factor has not been explored. This paper describes development of a spacecraft representing the first use of a 1 U CubeSat platform for aircraft tracking. To comply with the platform's limited power budget, the receiver departs from the typical application of FPGA boards to decoding ADS‐B signals and instead employs a general microprocessor. The spacecraft also features some innovations over traditional CubeSat platforms, such as distributed system‐level software amenable to extensive code reuse, redundant communications mechanisms, and software‐based radiation mitigation strategies. Having designed, built, and integrated all subsystems, as well as performed multiple test campaigns at system and subsystem level, the team now aims at completing formal functional and environmental testing before undergoing the launch campaign, foreseen for 2022.